2023
DOI: 10.3390/atmos14101532
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Effects through MFDFA Study of Temperature in Serbia

Tatijana Stosic,
Borko Stosic,
Milica Tošić
et al.

Abstract: We investigate multifractal properties of daily means of air temperature over the territory of Serbia, by using Multifractal detrended fluctuation analysis. Temperature anomalies in two periods 1961–1990 and 1991–2020 are calculated from the E-OBSv26.0e gridded dataset with 0.10° (~12 km) resolution, totaling 1278 daily temperature series for each period. The MFDFA parameters: position of the maximum of the spectrum α0, width of the spectrum W and asymmetry r, obtained from the total of 2556 MFDFA runs are int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Ionita and Nagavciuc [16] found that negative trends in drought (based on SPEI-12) in the Central Europe (CEU) and the Mediterranean region (MED) where Serbia is located are due to an increase in the potential evapotranspiration and mean air temperature. Our results support these findings in the sense that changes in multifractal properties from the first to the second sub-period of SPEI temporal series coincide with changes of multifractal properties of temperature series as reported in [63]. The multifractal properties of drought indices were investigated only recently.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Ionita and Nagavciuc [16] found that negative trends in drought (based on SPEI-12) in the Central Europe (CEU) and the Mediterranean region (MED) where Serbia is located are due to an increase in the potential evapotranspiration and mean air temperature. Our results support these findings in the sense that changes in multifractal properties from the first to the second sub-period of SPEI temporal series coincide with changes of multifractal properties of temperature series as reported in [63]. The multifractal properties of drought indices were investigated only recently.…”
Section: Resultssupporting
confidence: 90%
“…SPEI-12 series become less anti-persistent (approaching the random regime) and more complex in northern part of the country, indicating that long term dry/wet conditions become more difficult for modeling and prediction. Recently we investigated the changes in multifractality of air temperature across Serbia for the same sub-periods and using the same gridded dataset [63], and we found that in the second sub-period the persistence of temperature series increased across the whole country, the width of the spectrum increased in the northern and decreased in the central and southern parts of country, and that in both periods the multifractality is dominated by small fluctuations (right skewed ( ) spectrum), indicating the increase of complexity in the northern part of the country. The SPEI time series also showed increase in persistence in the second period for short term and medium-term dry/wet conditions (SPEI-1, SPEI-3 and SPEI-6), while long term dry/wet conditions described by SPEI-12 showed similar changes in the degree of multifractality as temperature series: an increase in the multifractality degree (increase of ) in the northern part, and decrease in multifractality degree (decrease of ) in the southern part of country.…”
Section: Resultsmentioning
confidence: 99%
“…A determinant factor when choosing which method to apply was the number of available input parameters; the model would be more complex if it had a greater number of parameters. The chosen method in the present study is easy to apply and has been widely referenced in the recent literature [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%